Spotty liver disease adversely affect the gut microbiota of layers hen - Van, Thi Thu Hao; Lee Nen That, Lisa F. M.; Perera, Rachelle; Anwar, Arif; Wilson, Timothy B.; Scott, Peter C.; Stanley, Dragana; Moore, Robert J. (Frontiers in Veterinary Science, 2022)
Spotty Liver Disease (SLD) is a serious infectious disease which occurs mainly in laying chickens in free range production systems. SLD outbreaks can increase mortality and decrease egg production of chickens, adversely impact welfare and cause economic hardship for poultry producers. The bacterium Campylobacter hepaticus is the primary cause of the disease. This study aimed to identify the effects of C. hepaticus on chicken gut microbiota and gut structure. Three C. hepaticus strains (HV10T, NSW44L and QLD19L), isolated from different states of Australia, were used in the study. Chickens at 26-weeks post-hatch were orally dosed with one of the C. hepaticus strains (challenged groups) or Brucella broth (unchallenged or control group). Six days after the challenge, birds were necropsied to assess liver damage, and caecal content and tissue samples were collected for histology, microbiology, and 16S rRNA gene amplicon sequencing to characterize the composition of the bacterial microbiota. Strain C. hepaticus NSW44L produced significantly more disease compared to the other C. hepaticus strains and this coincided with more adverse changes observed in the caecal microbiota of the birds challenged with this strain compared to the control group. Microbial diversity determined by Shannon and Simpson alpha diversity indices was lower in the NSW44L challenged groups compared to the control group (p = 0.009 and 0.0233 respectively, at genus level). Short-chain fatty acids (SCFAs) producing bacteria Faecalibacterium, Bifidobacterium and Megamonas were significantly reduced in the challenged groups compared to the unchallenged control group. Although SLD-induction affected the gut microbiota of chickens, their small intestine morphology was not noticeably affected as there were no significant differences in the villus height or ratio of villus height and crypt depth. As gut health plays a pivotal role in the overall health and productivity of chickens, approaches to improve the gut health of the birds during SLD outbreaks such as through diet and keeping the causes of stress to a minimum, may represent significant ways to alleviate the impact of SLD.